Multimorbidity in the Brazilian adult population: Protocol for a systematic review and meta-analysis of prevalence - Cristina Camargo Pereira; Larissa Silva Magalhães; Sandro Rogério Rodrigues Batista; Valéria Pagotto; Rafael Alves Guimarães (PLoS ONE, 2026)
Multimorbidity (MM), defined as the co-occurrence of multiple chronic conditions in a single individual, poses a major challenge to health systems. Its consequences include higher morbidity and mortality rates, reduced quality of life, and increased healthcare costs. Despite its substantial public health burden, no systematic reviews have comprehensively assessed the pooled prevalence of MM in Brazil. This manuscript outlines a protocol for a systematic review and meta-analysis aimed at estimating the prevalence of MM among community-dwelling adults in Brazil. We will conduct a systematic review and meta-analysis of population-based studies reporting MM prevalence in community settings. A comprehensive search will be performed in PubMed, Scopus, Web of Science, Embase, LILACS, and SciELO databases. Two independent reviewers will screen articles, assess study quality using the Joanna Briggs Institute (JBI) Checklist for prevalence studies, and extract data. For the meta-analysis, pooled estimates will be calculated using random-effects models with Restricted Maximum Likelihood (REML) estimators to account for between-study variability. Heterogeneity will be assessed using the I² statistic and Cochran’s Q test. Subgroups analyses (e.g., age group, sex, region, and study type) will be conducted where feasible. Findings will be reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The protocol is registered with the International Prospective Register of Systematic Reviews (CRD42024389106). This review will provide comprehensive evidence on MM prevalence in Brazil, identifying the burden of this problem for future research and informing public health strategies.